Exploring Tourist Commitment: Willingness to Pay for Mangrove Ecotourism in Sungsang IV Village, Banyuasin - Dessy Adriani; Trisna Wahyu Swasdiningrum Putri; Erika Febrianti (Postgraduate, University of Mataram, 2025)
The mangrove ecosystem in Sungsang IV Village, South Sumatra has degraded mainly due to climate change. To address this, a strategy for managing and conserving mangrove ecotourism is needed, emphasizing the role of tourists in generating economic value. Willingness to Pay (WTP) is an approach that can be used to measure economic value based on tourists' willingness to pay as an effort to develop mangrove ecotourism. The Contingent Valuation Model (CVM) in assessing WTP is used to project the economic value of the environment, especially benefits that are not available in the market. Factors that influence tourist WTP can be identified by binary logistic regression analysis. The average WTP value of mangrove ecotourism tourists is IDR 17,333 or IDR 17,500 per tourist per four months or IDR 52,500 per tourist per year. Factors that significantly influence WTP are age and cost of getting to the location. One strategy that can be done for the development of mangrove ecotourism in Sungsang IV Village is to utilize programs to overcome climate change in developing mangrove ecotourism. This study’s findings will help policy makers in promoting mangrove conservation and enhaching local community livelihoods.